Characteristics and scope of humanitarian relief forensic medical evaluations for immigrant children in the US. (August 2021) - Rosenberg, Julia; Edwards, Emily; Wang, Karen H.; McKenzie, Katherine C.; Asnes, Andrea G.; Young, Janine
Abstract: According to US Customs and Border Protection, over 473, 000 family units and 76, 000 unaccompanied children were apprehended in 2019, a multi-fold increase from previous years. Thus, the number of children who may be eligible for humanitarian relief has increased significantly. For those claiming humanitarian relief, forensic medical evaluations performed by health professionals can provide critical evidence to bolster claims. In this cross-sectional, nationwide survey—in which we sought to characterize specialties, forensic training, capacity, and scope of humanitarian relief evaluations for immigrant children under eighteen-years-old—only 28 providers, half of whom were Child Abuse Pediatricians, reported performing humanitarian relief evaluations. The most common reported type of humanitarian relief evaluation conducted was for asylum. We found that the current training for forensic medical evaluations for humanitarian relief in pediatrics is likely varied not well-defined, and not pediatric-specific. In order to protect the rights of children who are eligible for humanitarian relief, pediatric and family medicine forensic medical evaluation training standards and curricula need to be developed; validated humanitarian relief screening tools need to be tested and utilized; and residents and attending physicians, including specialists with expertise in forensic evaluations, need to be actively recruited to perform these evaluations in collaboration with legal aid organizations. Highlights: The number of children eligible for humanitarian relief has increased. Forensic medical evaluations by health professionals bolster claims. In this cross-sectional survey, 28 providers reported performing evaluations. Half of those who had performed an evaluation were Child Abuse Pediatricians. Forensic medical evaluation training in pediatrics is varied.